Seismic site characterization at the western Cephalonia Island in the aftermath of the 2014 earthquake series - Kassaras, I.; Papadimitriou, P.; V. Kapetanidis; Voulgaris, N. (International Journal of Geo-Engineering, 2017)
The site response during a strong earthquake event may be proven crucial for earthquake hazard assessment and risk mitigation. Two moderate magnitude earthquakes that occurred in early 2014 in Cephalonia produced the largest ground motion values ever recorded in Greece, highly exceeding the provisions of the effective seismic code implying for local effects. This motivated the investigation of site response in the epicentral area presented herein.